Sputum Conversion is Faster with Vitamin D Suplementation in Pulmonary TB Patients - Nita Andriani Lubis; Gabriella Septiani Nasution (Humanistic Network for Science and Technology (HNST), 2019)
Pulmonary tuberculosis (TB) is still a problem that must be resolved in Indonesia, especially North Sumatra. The study aims to determine the effect of vitamin D supplementation on the speed of sputum conversion in pulmonary TB patients. Randomized controlled trial study was conducted on 41 pulmonary TB patients according to inclusion criteria. Research subjects were given TB drug (DOTS program) and vitamin D treatment for 2 months. Sputum examination based on smear was carried out microscopically at 2nd week, 4nd week, 6nd week, and 8nd week after treatment. The results showed that all pulmonary TB patients who were given the intervention experienced sputum conversion. Research subjects with AFB +1 occurred the fastest conversion compared to the others. Statistical analysis using chi square obtained significant results (p = 0.0001). Sputum conversion evaluation based on the initial AFB status, there was a significant relationship between the time of sputum conversion with the initial AFB status with a very strong correlation level (r = 0.767). Vitamin D has been shown to have a significant effect on the patient's sputum conversion. Keywords: pulmonary TB; vitamin D; sputum conversion